Ten‐year reinvestigation of ocular manifestations in Marfan syndrome. (11th November 2018) - Sandvik, Gunhild F.; Vanem, Thy T.; Rand‐Hendriksen, Svend; Cholidis, Symira; Sæthre, Marit; Drolsum, Liv
Abstract : Importance: Long‐term follow‐up of Marfan syndrome (MFS) patients. Background: Investigate changes in ocular features in MFS patients fulfilling the Ghent‐2 criteria following a period of 10 years. Design: Repeated cross‐sectional study with two observations. Participants: Eighty‐four MFS patients were investigated in 2003‐2004 (baseline). Forty‐four of these patients (52%) were examined after 10 years. Methods: A comprehensive ocular examination performed at baseline and follow‐up. Main Outcome Measures: Development or progression of ectopia lentis (EL). Results: At follow‐up, mean age was 50.1 ± 11.9 years (range: 30‐80 years), 74% were female and 70% of the patients were diagnosed with EL compared to 66% at baseline. Two patients (3 eyes) had developed EL over the decade, representing a 13% risk. Furthermore, one eye had progressed from a subtle tilt of the lens to dislocation. We found no significant change in the axial length ( P = 0.96), the corneal curvature ( P = 0.64) or the spherical equivalent ( P = 0.23). Best corrected visual acuity was improved at follow‐up ( P = 0.02). There were 7% and 33% risks for development of retinal detachment and cataract between baseline and follow‐up, respectively. Conclusions and Relevance: Our study indicates that even though EL typically occurs at an early stage in most MFS patients, there is still a risk of developing EL in adulthood. The risk of developing vision‐threatening complications such as retinal detachment and cataract was much higher than in the normal population, but even so, the visual potential of the MFS patients was relatively good.